(untitled) (United States of America, 2007)
This twenty-seventh edition of annual editions: World Politics provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor’s resource guide with testing materials. Using Annual editions in the classrom is offered as a practical guide for instructors. Annual editions titles are supported by our student website, www.dushkin.com/online.
Keywords: Chính trị thế giới,World politics